2018
DOI: 10.1017/s0007485318000470
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of prophenoloxidase-1 (PPO1) and the inhibitory effect of kojic acid on phenoloxidase (PO) activity and on the development ofZeugodacus tau(Walker) (Diptera: Tephritidae)

Abstract: Phenoloxidase (PO) plays a key role in melanin biosynthesis during insect development. Here, we isolated the 2310-bp full-length cDNA of PPO1 from Zeugodacus tau, a destructive horticultural pest. qRT-polymerase chain reaction showed that the ZtPPO1 transcripts were highly expressed during larval-prepupal transition and in the haemolymph. When the larvae were fed a 1.66% kojic acid (KA)-containing diet, the levels of the ZtPPO1 transcripts significantly increased by 2.79- and 3.39-fold in the whole larvae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
(62 reference statements)
2
7
0
Order By: Relevance
“…They have been implicated in several processes of insect physiology such as melanization, cuticular hardening, pathogen encapsulation, wound healing, and overall immunity (Binggeli, Neyen, Poidevin, & Lemaitre, 2014). Several studies have demonstrated that kojic acid‐based inhibition of PPOs is associated with a significant decrease in insect fitness and development (Alverson, 2003; Bai et al., 2014; Zhang, Luo, et al., 2019). Because PPOs play key roles in the defensive system of insects, they are an attractive target to implement insect control strategies.…”
Section: Aspergillus Flavus Linkmentioning
confidence: 99%
“…They have been implicated in several processes of insect physiology such as melanization, cuticular hardening, pathogen encapsulation, wound healing, and overall immunity (Binggeli, Neyen, Poidevin, & Lemaitre, 2014). Several studies have demonstrated that kojic acid‐based inhibition of PPOs is associated with a significant decrease in insect fitness and development (Alverson, 2003; Bai et al., 2014; Zhang, Luo, et al., 2019). Because PPOs play key roles in the defensive system of insects, they are an attractive target to implement insect control strategies.…”
Section: Aspergillus Flavus Linkmentioning
confidence: 99%
“…Enzymes and genes associated to pigmentations of insects were searched and identificated based on studies reported. There were 9 families of enzymes or genes as follow: Dopachrome converting enzyme family DEC(yellow) Futahashi et al, 2008;Ferguson et al, 2011;Futahashi et al, 2012), N-acetyltransferase(AANAT) (Hintermann et al, 1996;Tsugehara et al, 2007;Zhang et al, 2018b), Phenoloxidase(laccase2) (Futahashi et al, 2010;Yatsu et al, 2009;Futahashi et al, 2010), NBAD synthetase (ebony) (Hovemann et al, 1998;Richardt et al, 2002;Wittkopp et al, 2002;Futahashi et al, 2008;Pool et al, 2010;Takahashi et al, 2011;Ferguson et al, 2011;Zhang et al, 2018b), NBAD hydrolase (tan) (Futahashi et al, 2010;Ferguson et al, 2011;Du et al, 2018), Phenoloxidase(PO) (Zhang et al, 1997;Luna et al, 2011;Sachdev et al, 2017;Zhang et al, 2018a), Aspartate decarboxylase (ADC) (Arakane et al, 2009;Dai et al, 2015), DOPA decarboxylase (DDC\AADC) (Fang et al, 2000;Hawi et al, 2001;Chen et al, 2002;Ma et al, 2005;Yu et al, 2006;Giegling et al, 2008;Paskewitz et al, 2008;Bertoldi et al, 2009;Ferguson et al, 2011;Geomela et al, 2012), Phenylalanine hydroxylase(PAH) (Kwok et al, 1985;Johnson et al, 2003;Infanger et al, 2004;…”
Section: Indentifications Of Genes In Different Gene Familiesmentioning
confidence: 99%
“…The formation of melanin was related to contents of substances including phenylalanine, tyrosine, DOPA, N-acetyl-dopamine (NADA), N-beta-alanyl-dopamine (NBAD) Sekine et al, 2011) and so on. These substances were related to some enzymes including phenylalanine hydroxylase (PAH) (Kwok et al, 1985;Zhang, 2004;Infanger et al, 2004), TH (Futahashi et al, 2008), DDC(Fang et al, 2000;Chen et al, 2002;Paskewitz et al, 2008;Giegling et al, 2008;Bertoldi et al, 2009;Ferguson et al, 2011;Hodges et al, 2012), PO (Sachdev et al, 2017;Zhang et al, 2018a), Phenoloxidase(laccase2) (Yatsu et al, 2009;Futahashi et al, 2010), NBAD synthetase (ebony) (Hovemann et al, 1998;Wittkopp et al, 2002;Takahashi et al, 2008;Takahashi et al, 2011;Ferguson et al, 2011), NBAD hydrolase (tan) (Futahashi et al, 2010;Wagner et al, 2010;Du et al, 2018), dopachrome conversion enzyme family (yellow) Futahashi et al, 2008;Ferguson et al, 2011;Futahashi et al, 2012), aspartate decarboxylase (ADC) (Arakane et al, 2009;Dai et al, 2015) and arylalkylamine-N-acetyltransferase (AANAT) (Hintermann et al, 1996;Tsugehara et al, 2007;Zhan et al, 2010;Zhang et al, 2018b). These enzymes and genes were mostly studied on the growing developments of insects (Bai et al, 2014;Sachdev et al, 2017;Zhang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes and genes associated to pigmentations of insects were searched and identificated based on studies reported. There were 9 families of enzymes or genes as follow: Dopachrome converting enzyme family DEC(yellow) Futahashi et al, 2008;Ferguson et al, 2011;Futahashi et al, 2012), N-acetyltransferase(AANAT) (Hintermann et al, 1996;Tsugehara et al, 2007;Zhang et al, 2018b), Phenoloxidase(laccase2) (Futahashi et al, 2010;Yatsu et al, 2009;Futahashi et al, 2010), NBAD synthetase (ebony) (Hovemann et al, 1998;Richardt et al, 2002;Wittkopp et al, 2002;Futahashi et al, 2008;Pool et al, 2010;Takahashi et al, 2011;Ferguson et al, 2011;Zhang et al, 2018b), NBAD hydrolase (tan) (Futahashi et al, 2010;Ferguson et al, 2011;Du et al, 2018), Phenoloxidase(PO) (Zhang et al, 1997;Luna et al, 2011;Sachdev et al, 2017;Zhang et al, 2018a), Aspartate decarboxylase (ADC) (Arakane et al, 2009;Dai et al, 2015), DOPA decarboxylase (DDC\AADC) (Fang et al, 2000;Hawi et al, 2001;Chen et al, 2002;Ma et al, 2005;Yu et al, 2006;Giegling et al, 2008;Paskewitz et al, 2008;Bertoldi et al, 2009;Ferguson et al, 2011;Geomela et al, 2012), Phenylalanine hydroxylase(PAH) (Kwok et al, 1985;Johnson et al, 2003;Infanger et al, 2004;Zhang et al, 2004;Wang et al, 2013)…”
Section: Indentifications Of Genes In Different Gene Familiesmentioning
confidence: 99%